Power from Pellets Technology and Applications - Döring, Stefan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book provides a practical description of the technology of pellet production on the basis of renewable sources as well as the utilization of pellets. The author explains what kinds of biomass are usable in addition to wood, how to produce pellets and how to use pellets to produce energy. Starting with the basics of combustion, gasification and the pelletizing process, several different technologies are described. The design, planning, construction and economic efficiency are discussed as well. The appendix gives useful advice about plant concepts, calculations, addresses, conversion tables and formulas.
Biomasses for Pellet Production -- Combustion Characteristics -- Legal Requirements for Using Wood Pellets for Providing Heat -- Fuel Quality Requirements -- Wood Pellet Production -- Using Wood Pellets as an Energy Source -- Protection against Fire and Explosions -- Profitability of Pellet Boilers -- Research and Development.
Keywords: Energy systems; Renewable energy resources; Industrial engineering; Production engineering; Energy Systems; Renewable and Green Energy; Industrial and Production Engineering